New classification for the treatment of pyogenic spondylodiscitis: validation study on a population of 250 patients with a follow-up of 2 years - Pola, Enrico; Cipolloni, Valerio; Nasto, Luigi Aurelio; Piccone, Luca; Formica, Virginia; Pambianco, Virginia; Colangelo, Debora; Fantoni, Massimo (Lo Scalpello - Journal, 2022)
Objective. Pyogenic spondylodiscitis (PS) is still burdened by a high rate of orthopedic and neurological complications. Despite its rising incidence, the choice of proper orthopedic treatment is often delayed by the lack of clinical data. The aim of this study was to propose a clinical-radiological classification of PS to define a standard treatment algorithm. Methods. Based on data from 250 patients treated from 2008 to 2015, a clinical-radiological classification of PS was developed. According to primary classification criteria (bone destruction or segmental instability, epidural abscesses, and neurological impairment), three main classes were identified. Subclasses were defined according to secondary criteria. PS without segmental instability or neurological impairment was treated conservatively. When significant bone loss or neurological impairment occurred, surgical stabilization and/or decompression were performed. All patients underwent clinical and radiological 2-year follow-up. Results. Type A PS occurred in 84 patients, while 46 cases were classified as type B and 120 as type C. Average time of hospitalization was 51.94 days and the overall healing rate was 92.80%. 140 patients (56.00%) were treated conservatively with average time of immobilization of 218.17 ± 9.89 days. Both VAS and SF-12 scores improved over time in all classes. Residual chronic back pain was present in 27 patients (10.80%). Overall mortality was 4.80%. Conclusions. Standardized treatment of PS is highly recommended to ensure patients a good quality of life. The proposed scheme includes all available orthopedic treatments and helps spine surgeons to significantly reduce complications and costs and avoid overtreatment.